Transnational business strategies of Serbian entrepreneurs in Vienna - Antonijević Dragana; Rašić Miloš; Barać Lazar (Glasnik Etnografskog Instituta SANU, 2025)
This paper explores the transnational business strategies of Serbian entrepreneurs in Vienna by analyzing their migration trajectories, social networks, and business models. The study is based on ethnographic research and data collected through semi-structured in-depth interviews conducted with Serbian entrepreneurs in Vienna. By examining the narratives of the respondents, the paper identifies key patterns in their entrepreneurial practices, including reliance on social networks, adaptation to the Austrian business environment, and the maintenance of economic ties with Serbia and other countries where they operate. The main findings suggest that Serbian entrepreneurs in Vienna actively engage in the creation of transnational economic spaces, integrating resources, knowledge, and market strategies across two or more countries.